Cattle productivity and carbon stock in silvopastoral systems with Leucaena in the colombian dry caribbean (2019)
Dual-purpose cattle systems in the Cesar Valley microregion are based on grazing for grasses and grasslands. In the region, the grass Colosuana (Bothriochloa pertusa) is the predominant grass that is usually associated with low milk yield in dual-purpose cows. The integration of shrubs and trees for different purposes in grazing areas is still occasionally adopted by farmers.